Outcomes of donor-derived superinfection screening in HIV-positive to HIV-positive kidney and liver transplantation: a multicentre, prospective, observational study. Issue 9 (September 2020) - Bonny, Tania S; Kirby, Charles; Martens, Craig; Rose, Rebecca; Desai, Niraj; Seisa, Michael; Petropoulos, Christos; Florman, Sander; Friedman-Moraco, Rachel J; Turgeon, Nicole A; Brown, Diane; Segev, Dorry L; et al.
Summary: Background: One of the primary risks of HIV-positive to HIV-positive organ transplantation is loss of virological control because of donor-derived HIV superinfection, which occurs when an HIV-positive individual becomes infected with a new distinct HIV strain. In this study, as part of the larger HIV Organ Policy Equity pilot study, HIV-positive to HIV-positive kidney and liver transplant recipients in the USA were examined for evidence of sustained donor-derived HIV superinfection. Methods: In this multicentre, prospective, observational study, HIV-positive to HIV-positive kidney and liver transplant recipients were followed in three hospitals in the USA. Candidates with well controlled HIV infection on ART, no active opportunistic infections, and minimum CD4 T-cell counts (>100 cells per μL for liver and >200 cells per μL for kidney per federal guidelines) were eligible to receive a kidney or liver from deceased HIV-positive donors without active infections or neoplasm. Peripheral blood mononuclear cells were collected from donor–recipient pairs at the time of transplantation, and from recipients at several timepoints up to 3 years after transplantation. Donor samples were assessed for HIV RNA viral load, CD4 cell count, and antiretroviral drug-resistant mutations. Donor and recipient HIV proviral DNA, and viral RNA from the viraemic timepoint were sequenced using a site-directed next-generation sequencing assay for the reverse transcriptase and gp41 genes. Neighbour-joining phylogenetic trees and direct sequence comparison were used to detect the presence of HIV superinfection. This study is registered with ClinicalTrials.gov, NCT02602262 . Findings: 14 HIV-positive to HIV-positive kidney and eight liver transplant recipients were followed from March, 2016, to July, 2019. 17 recipients had adequate viral sequences allowing for HIV superinfection assessment. Eight donors were suppressed (viral load <400 copies per mL), and none had multiclass drug-resistant mutations detected. None of the recipients examined had evidence of HIV superinfection. One recipient had a viraemic episode (viral load of 2 080 000 copies per mL) 3 years after transplantation as a result of non-adherence to ART. Only recipient viral sequences were detected during the viraemic episode, suggesting that the donor virus, if present, was not reactivated despite temporary withdrawal of ART. Interpretation: These findings suggest that loss of HIV suppression due to donor-derived HIV superinfection might not be a significant clinical concern in carefully monitored ART suppressed HIV-positive organ recipients. Funding: US National Institute of Allergy and Infectious Diseases and National Cancer Institute.